Status of English language teaching in secondary level under different school interventions - Adhikari, Deepika (Journal of NELTA, 2019)
Language is the primary medium of communication and expression of thoughts and ideas. In India, there are two official languages- Hindi and English. English has-been occupying a dominant position since independence. There have been serious attempts to integrate English language in the school curriculum since 1980s. In the schools of West Bengal, English is taught either as a first language or second language. The present study intends to find the status of teaching English language in the secondary schools of Siliguri (West Bengal) where the schools with three different boards, ICSE, CBSE and state boards are chosen. The sample consisted of 50 teachers and 50 students from a total of 25 schools. A survey method and observation inventory was used for collection of data. The conclusion is that English language teachers need to abreast themselves with the latest developments in the context of language teaching. The co-operation from the school, teachers, parents and students yield fruitful results in improving the status of English language teaching.